Market run-ups, market freezes, inventories, and leverage - Bond, Philip; Leitner, Yaron (Journal of Financial Economics, 2015)
We study trade between an informed seller and an uninformed buyer who have existing inventories of assets similar to those being traded. We show that these inventories could induce the buyer to increase the price (a run-up) but could also make trade impossible (a freeze) and hamper information dissemination. Competition can amplify the run-up by inducing buyers to purchase assets at a loss to prevent competitors from purchasing at lower prices and releasing bad news about inventories. In a dynamic extension, we show that a market freeze could be preceded by high prices. Finally, we discuss empirical and policy implications.